Radiation management of a late thoracic metastasis from an intracranial solitary fibrous tumour. Issue 11 (10th November 2022) - Patel, Arjun; Palma, David; Sangle, Nikhil; Zayed, Sondos
Abstract : Solitary fibrous tumours (SFTs) are a rare soft tissue sarcoma. We present a case of a male patient with an SFT of the right posterior fossa, with a late metastasis to the right lung and chest wall identified 18 years later. A small number of late metastases of SFTs have previously been reported. Metastases are typically managed surgically, although there is limited evidence suggesting that radiotherapy may be effective for primary SFTs. In this case, the patient declined treatment for his metastasised cancer for 5 years. He then only agreed to radiation treatment without surgery, which uniquely resulted in excellent symptom relief and durable local control. This case illustrates the importance of further research on the role of radiation in managing SFTs, the value of long-term follow-up and the necessity of exploring barriers to care. This case also highlights issues regarding barriers to care related to late diagnoses of recurrence in rare tumours. In this case, at the time of recurrence the original tissue blocks were not available for review. The patient had moved to a different province where his former records were not easily accessible, and the original tissue blocks had been discarded. In that jurisdiction, laboratories must keep cytology slides for 5 years, histopathology slides for 10 years and paraffin blocks for 2 years. This contributed to a misdiagnosis of the recurrence as an Ewing sarcoma, resulting in the patient initially declining treatment at the time of disease recurrence, and leading to a long-standing mistrust of his physicians which impacted his decision-making.